Noninvasive diagnostic modality for skin cancer - Siregar, Remenda; Nurhayati, Raja; Oentari, Widyaningsih; Sari, Ari Karmila (UI Scholars Hub, 2021)
Histopathological examination is the gold standard for the diagnosis of nonmelanoma and melanoma skin cancer, but it is an invasive procedure that consumes time and requires large costs. The average cure rate for skin cancer is high with early detection and appropriate treatment. This is an article review that was made through findings from several scientific articles. There are several noninvasive imaging modality choices that can be used for screening at low cost, high quality, and faster result, which includes dermoscopy, optical coherence tomography, reflectance confocal microscopy, electrical impedance spectroscopy, multispectral imaging, and SIAscopy®. These imaging modalities can assist in the detection of skin cancer using a combination of high-quality computer science, mathematics, and optics. This can improve the efficiency of diagnosis and management, reduce treatment costs, and increase patient satisfaction while utilizing teledermatology.